Predicting depression based on emotional intelligence and critical thinking in women with narcissistic personality disorder - Seyed Ahmad Harati, Vahidesadat; Parisa Zare (Psychology of Woman Journal, 2022)
Narcissism is a personality disorder that is conceptualized as excessive self-love and manifests as a great sense of self, more entitlement, and superiority. Its prevalence is much higher in women than in men. This study aimed to investigate the prediction of depression based on emotional intelligence and critical thinking in women with a narcissistic personality disorder. The current research is part of applied research in terms of its purpose and correlational studies in terms of method. The statistical population included all women with narcissistic personality disorder referred to Nik Amal Psychotherapy Clinic in Tehran in 2021. 130 people were selected as a sample using the available sampling method. Ames Narcissistic Personality Questionnaire (2006), Beck Depression Questionnaire (1961), Schering Emotional Intelligence Test (1996), and California Critical Thinking Skills Test, Form B (1990) were implemented on them. Data analysis was done with correlation and regression tests using SPSS version 23 software. A significance level of less than 0.05 was considered. The results showed that emotional intelligence and critical thinking have a negative and significant relationship with depression (P